Lipid Profile in Postmenopausal Diabetic Female. - Simkhada, Rabindra; KC, Sanjay Singh; Yadav, Dharma Nath; Sahi, Ravi (Nepalese Heart Journal, 2021)
Background and Aims: Postmenopausal diabetic female are at increased risk of cardiovascular disease. The objective of this study was to study their lipid profile and prevalence of dyslipidemia and assess relation of control of lipid components with various risk factors.Methods: A cross sectional prospective study conducted at Shahid Gangalal National Heart Centre from 15th July 2020 to 14th October 2020 including 109 postmenopausal diabetic female. Detailed history along with clinical examination were conducted. Fasting lipid profile and other relevant investigations were obtained.Results: Mean age of participants was 63.48±9.26 years. Mean age of menopause was 48.59±1.88 years. A total of 37 (33.9%) were hypertensive, 17 (15.6%) were smoker, 67 (61.5%) were physically inactive. A total of 91 (83.5%) were non-vegetarian. Thirty eight (34.9%) had their blood sugar controlled with hemoglobin A1c of